2020
DOI: 10.3390/antibiotics9060330
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Role of Amino Acids in Microbial Control and Drug Development

Abstract: Amino acids are ubiquitous vital biomolecules found in all kinds of living organisms including those in the microbial world. They are utilised as nutrients and control many biological functions in microorganisms such as cell division, cell wall formation, cell growth and metabolism, intermicrobial communication (quorum sensing), and microbial-host interactions. Amino acids in the form of enzymes also play a key role in enabling microbes to resist antimicrobial drugs. Antimicrobial resistance (AMR) and microbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 158 publications
0
32
0
Order By: Relevance
“…Regarding the precise function of amino acids in the response of plants to pathogens, it is not well established: on one hand, they are required for growth and metabolism in microorganisms, and on the other hand, careful optimization of composition and concentration can produce antimicrobial effects [56]. Besides this, changes in the contents of amino acids appear to be a common characteristic of plant response to GTDs.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Regarding the precise function of amino acids in the response of plants to pathogens, it is not well established: on one hand, they are required for growth and metabolism in microorganisms, and on the other hand, careful optimization of composition and concentration can produce antimicrobial effects [56]. Besides this, changes in the contents of amino acids appear to be a common characteristic of plant response to GTDs.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“… Depiction of Staphylococcus aureus biofilm formation on an abiotic surface. Basic concept has been adopted from Idrees et al (2020) and Paharik (2016) [ 7 , 26 ]. …”
Section: Figurementioning
confidence: 99%
“…Similar to any other bacterial biofilm, a Staphylococcus aureus biofilm also has two distinct components, i.e., water (about 97%) and the organic matter which includes EPS and microcolonies [ 5 ]. The EPS constitutes about 50 to 90% of the total organic matter of a biofilm and is a complex of different polymeric substances, such as extracellular DNA (eDNA), proteins and polysaccharides [ 6 , 7 ]. The remaining portion, 10–25%, consists of microcolonies [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amino acids (AA) are versatile molecules which have a multitude of functions and can be used as anti-biofilm agents, drug excipients, drug solubility enhancers, and drug adjuvants [ 1 ]. Previously, it has been shown that both D- and L-isoforms of acidic amino acids are able to exhibit anti-biofilm activity on their own and act synergistically with Ciprofloxacin (Cip) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%